UN VIAJE A TRAVÉS DE LA HISTORIA. EL TREN DE LAS OLIMPIADAS . (Campo Abierto. Revista de Educación y Psicología, 2016)
This work attempts to presenta didactic apprach to the teaching and understanting of chonology and history in the third level of Primary Education.